Development of next generation antibody-based immunotherapy for childhood cancer neuroblastoma. (25th February 2016) - Patel, Aysha; Thevanesan, Christine; Anderson, John; Pule, Martin; Straathof, Karin
Abstract: Background: High risk neuroblastoma poses a significant clinical problem in paediatric oncology and new treatment strategies are needed. Antibody therapy specific for neuroblastoma surface molecule GD2 has been shown to improve outcome. Here we develop a new generation antibody-based therapeutic agent named BiTE (Bi-specific T cell Engager) that combines antibody specificity with potent T cell functions. Methods: To identify the BiTE format with maximum activity against neuroblastoma, BiTEs were constructed with single chain variable fragments (scFv) derived from three different CD3-specific antibodies, scFv from two different GD2-specific antibodies, and three different flexible linkers between these CD3 (ie, T cell) and GD2 (ie, neuroblastoma) binders. Specific binding to CD3-positive and GD2-positive cell lines and cytolytic activity at a range of BiTE concentrations was assessed. Findings: Seven different BiTE formats have been successfully produced and purified. Whereas all seven BiTEs constructed showed binding to GD2-positive and CD3-positive cell lines and absence of binding to target antigen-negative cells, mean fluorescence intensity of CD3 binding (14·6 arbitrary units, 24·6, 255) and of GD2 binding (1366, 4258) indicated a range of affinities for CD3 and GD2. For each BiTE, lysis of GD2-target cells was only observed in the presence of T cells. Similarly, secretion of interferon γ by activated T cells only occurred in a CD3-specific and GD2-specific manner. All seven BiTEs induced GD2-specific cytolytic activity. Cytolytic activity was achieved at the lowest EC50 (ie, <1 ng/mL BiTE) for the BiTE format with highest GD2 affinity and moderate CD3 affinity. Interpretation: Our findings demonstrate that the optimum BiTE design for tumour targeting can be identified by functional testing of BiTE formats incorporating CD3-specific scFvs and tumour antigen-specific scFvs with a range of binding affinities. Our optimum BiTE construct shows remarkable in-vitro activity approaching that of blinatumomab, which has proven clinical activity against leukaemia; we aim to develop this BiTE into a new therapeutic agent for neuroblastoma. Funding: Great Ormond Street Hospital Institute of Child Health Biomedical Research Centre, Wellcome Trust.